Identificación de Diatomeas Epilíticas asociadas a la Calidad del Agua en el Río Yanayacu, sector San Juan, Cantón Salcedo, Provincia de Cotopaxi, 2020. - Maiquiza Ramírez, Katty Elizabeth (2020)
The purpose of the research project is to determine the water quality based on biological indicators present in Yanayacu river, San Miguel of Salcedo canton, Cotopaxi province, AT this study case it was possible to identify a total of 26 species of epilithic diatoms in the river; A sampling was carried out at the midpoint (San Juan), with an altitude of 2773 meters over sea level, in which the presence of 5 epilithic diatoms was found: Encyonema lange-bertalotti, Gomphonema pumilum var. rigidum, Gomphonema parvulum, Gomphonema rhombicum, Hantzschia bacillariophyta. To calculate the water quality index (ICA) in February, 9 physical-chemical and microbiological parameters were used (pH, Temperature, Turbidity, Dissolved Oxygen, Total Dissolved Solids, Fecal Coliforms, Nitrates, Phosphates, Biochemical Oxygen Demand “BOD5”), which were assessed through the IQAData program, where at the highpoint a result of 53,37 was obtained, considered a Regular rating, midpoint a result of 41.75 was obtained, considered a Bad rating, and lowpoint a result of 35,7 was obtained, considered a Bad rating, later the theoretical and table trophic index of water quality (ITCA) was compared; At the midpoint, the theoretical ITCA obtained a value of 2.0, which compared to the ITCA in the tables is in the range of 1.5 to 2.5, showing a moderate level of β-mesotrophic contamination. A comparison was made with different study cases located at Cotopaxi province of Cutuchi, Pumacunchi and Yanayacu rivers. The present study has a correlation with the Water Quality Trophic Index (ITCA) and the midpoint of the Cutuchi river micro-basin that assigns a β-mesotrophic rating - moderate contamination, while in the Water Quality Index (ICA) with a Bad rating, the same one that is not related to the midpoints of the Cutuchi (Regular rating), Pumacunchi and Yanayacu (Very Bad rating) rivers. It is worth mentioning that Pumacunchi and Yanayacu rivers flow into Cutuchi River from Latacunga Canton, as well as the Yanayacu River from Salcedo canton.